TOWARDS THE INTERNATIONAL FINANCIAL REPORTING STANDARD ADOPTION: A WILL OR A CONSTRAINT - Ahmadi, Ali (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2025)
ABSTRACTThis study aims to apply the adoption of Internatisonal Financial Reporting Standard (IFRS) which is one of the newest and most debated terms in accounting research in the last two decades. This study is a descriptive study with data sources derived from articles, accounting standard statements and other primary sources. The study result show the transition to international accounting standards (IFRS) has brought significant changes to financial reporting, including social reporting and the level of conservatism. While IFRS improves transparency and investment efficiency, challenges remain in balancing compliance with global standards with the need for sustainability-oriented reporting. This study contributes to the growing literature that investigates the adoption of IFRS in the new global economic order, societal consistency, and the relationship between accounting conservatism and investment policy effectiveness. One of the main objectives is to improve investors' perceptions of the value of assets acquired while replacing the concept of "historical cost" with "fair value".ABSTRAKPenelitian ini bertujuan untuk menerapkan adopsi Standar Pelaporan Keuangan Internasional (IFRS) yang merupakan salah satu istilah terbaru dan paling banyak diperdebatkan dalam penelitian akuntansi dalam dua dekade terakhir. Penelitian ini merupakan penelitian deskriptif dengan sumber data yang berasal dari artikel, pernyataan standar akuntansi, dan sumber primer lainnya. Hasil penelitian menunjukkan transisi ke standar akuntansi internasional (IFRS) telah membawa perubahan signifikan pada pelaporan keuangan, termasuk pelaporan sosial dan tingkat konservatisme. Sementara IFRS meningkatkan transparansi dan efisiensi investasi, tantangan tetap ada dalam menyeimbangkan kepatuhan terhadap standar global dengan kebutuhan pelaporan yang berorientasi pada keberlanjutan. Penelitian ini berkontribusi pada literatur yang berkembang yang menyelidiki adopsi IFRS dalam tatanan ekonomi global baru, konsistensi masyarakat, dan hubungan antara konservatisme akuntansi dan efektivitas kebijakan investasi. Salah satu tujuan utama adalah untuk meningkatkan persepsi investor terhadap nilai aset yang diperoleh sambil mengganti konsep "biaya historis" dengan "nilai wajar".